Interplay between the linker and polymer molecular weight of a self-assembling prodrug on the pharmacokinetics and therapeutic efficacy. (11th May 2022) - Nguyen, Anne; Rouhollahi, Elham; Böttger, Roland; Ong, Chun Yat; Chao, Po-Han; Wu, Jiamin; Chen, Yao; Li, Shyh-Dar
Abstract : We studied the interplay of polymer molecular weight and linker of self-assembling nanoparticles on the pharmacokinetics, safety, and efficacy. Abstract : Poorly water-soluble small hydrophobic compounds can be conjugated to a hydrophilic polymer such as methoxypolyethylene glycol (mPEG) to form amphiphilic prodrugs that can self-assemble into nanoparticles (NPs) with increased aqueous solubility, prolonged circulation, and improved delivery. There have been numerous reports utilizing this strategy to improve delivery of small molecule drugs, but few reports take systematic, structure–activity relationship (SAR)-based approaches to develop optimal prodrug conjugates. Additionally, it is important to study interplay of different components within the conjugate, such as polymer molecular weight (M.W.) and linker to obtain optimal efficacy and safety. In this study, we developed a click chemistry platform to conjugate mPEG of three different M.W. (low: 550 Da; medium: 2000 Da; high: 5000 Da) to a small molecular anti-tumor drug, gambogic acid (GA) via two different linkers (ester: fast release; amide: slow release) to generate six distinct conjugates. NPs formed from conjugates of mPEG550 displayed significantly higher hemolytic toxicity compared to those with higher M.W. (<10%), regardless of the linker type. Drug release studies showed that NPs with an amide linker displayed insignificant drug release (<0.5% per day) compared to those with an ester linker (1–2% per day). NPs formed with mPEG5000 using an ester linker (5000-E-NP) possessed the optimal balance between prolonged circulation (223-fold higher AUC1–24 h than free GA) and sufficient drug release (1.68 ± 0.13% per day), leading to superior anti-tumor efficacy compared to other formulations, while the corresponding amides (5000-A-NP) displayed the most prolonged circulation but only moderate efficacy likely due to insufficient drug release. Our work highlights the importance of diligently studying SAR on drug conjugates to improve drug delivery and confirms the robustness of using the click platform to generate a conjugate library with chemical diversity.